Identification of calcium chelating peptides from peanut protein hydrolysate and absorption activity of peptide–calcium complex - Bu, Guanhao; Zhao, Xiaoling; Wang, Mengli; Ti, Guanghui; Chen, Fusheng; Duan, Xiaojie; Huang, Yanan; Li, Panxin (Journal of the science of food and agriculture, 2024)
BACKGROUND Peanut peptides have good chelating ability with metal ions. However, there are few studies on the chelation mechanism of peanut peptides with calcium and absorption properties of peptide–calcium complex. RESULTS Peptides with high calcium chelating rate were isolated and purified from peanut protein hydrolysate (PPH), and the chelation rate of component F21 was higher (81.4 ± 0.8%). Six peptides were identified from component F21 by liquid chromatography–tandem mass spectrometry, and the frequency of acidic amino acids and arginine in the amino acid sequence was higher in all six peptides. Peanut peptide–calcium complex (PPH21‐Ca) was prepared by selecting component F21 (PPH21). Ultraviolet analysis indicated that the chelate reaction occurred between peanut peptide and calcium ions. Fourier transform infrared analysis showed that the chelating sites were carboxyl and amino groups on the amino acid residues of peptides. Scanning electron microscopy revealed that the surface of peanut peptide had a smooth block structure, but the surface of the complex had a granular morphology. Caco‐2 cell model tests revealed that the bioavailability of PPH21‐Ca was 58.4 ± 0.5%, which was significantly higher than that of inorganic calcium at 37.0 ± 0.4%. CONCLUSION Peanut peptides can chelate calcium ions by carboxyl and amino groups, and the peptide–calcium complex had higher bioavailability. This study provides a theoretical basis for the development of new calcium supplement products that are absorbed easily. © 2024 Society of Chemical Industry.